Changes in self-care following a family-based care intervention among patients with type 2 diabetes mellitus: A one-group pretest–posttest study - Chika Tiara Oktaviana; Ismonah Ismonah; Dwi Yogo Budi Prabowo (Lentera Perawat, 2026)
Background: Self-care is a fundamental component of diabetes management; however, many patients with type 2 diabetes mellitus demonstrate inadequate self-care practices. Family support plays an important role in promoting adherence to medication, dietary management, physical activity, blood glucose monitoring, and foot care, thereby supporting diabetes self-management. Objective: This study aimed to evaluate changes in self-care following a family-based care intervention among patients with type 2 diabetes mellitus. Methods: A quantitative pre-experimental study using a one-group pretest–posttest design was conducted among 30 patients with type 2 diabetes mellitus recruited through purposive sampling at Mijen Primary Health Center, Semarang, Indonesia. Participants received a two-week family-based care intervention consisting of structured family education during the first week and family monitoring during the second week. Self-care was assessed before the intervention and immediately after the intervention using the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. Data were analyzed using the Wilcoxon signed-rank test. Results: Most participants were aged 56–65 years (53.3%), female (56.7%), and had completed elementary school education (40.0%). Before the intervention, most participants were categorized as having fair self-care (53.3%), whereas after the intervention, most were categorized as having good self-care (63.3%). Wilcoxon signed-rank test showed a statistically significant difference between pretest and posttest self-care scores (Z = −4.963, p < 0.001). Conclusion: Participants demonstrated higher self-care scores following the family-based care intervention than before the intervention. These findings provide preliminary evidence that involving family members may support self-care among patients with type 2 diabetes mellitus in primary healthcare settings. Further controlled studies with larger samples and longer follow-up periods are needed to confirm the effectiveness of this intervention.